The research companion a practical guide for the social and health sciences - Boynton, Petra M. (Psychology Press, 2005)
"Social science research has traditionally focused on the historical study of research methods, frequently overlooking the practical skills needed to undertake a research project. The Research Companion addresses this need for instruction in the practice of research and offers clear, honest advice to help avoid typical problems and improve the standards. This book will be invaluable to all researchers in the social or health sciences, whatever their level of experience, making research more accurate, ethical and productive."--BOOK JACKET